Bridging Towards Political Power: China and the New Institutionalised Strategies - Shuluh Shasa Nadita (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2021)
Experiencing rapid economic growth backed by high-level leadership support, China exerts tight political influence and information control by using a new approach sharp power, encompassing strong economic fabric, political integrity, global transfer of people and knowledge. To compete in international competition—China has been using redistribution method to contest its power politics upon conducting collective repression on flouting democratic reform in Hong Kong, ethnic minority assimilation—Tibetan and Uighur, and One China Policy against Taiwan, to global campaign to dominate influence by political, economic and technological representations. The actions deliberately carry underlaying goals to define economic prosperity with the expense of political freedom. This research paper aims to deliberate key points on China’s endeavours to strengthen political power both internally and internationally with the averse to govern democracy—and construction on world politics by using economic power mostly in the cultural and technology inventories. This study used qualitative method through data collection techniques based on internet observation and library research. The using of sharp power concept as a novel approach coined by independent think tank National Endowment Democracy is conceived to delineate deep understanding on China’s political power by engaging other two underlying concepts as reinforcing instruments which support sharp power concept. The results of this research which shows China’s strategies are alternatively institutionalised through the emergence of economic assistance, technology, and socio-cultural instruments.